TI_GERICHTE 52.2023.360 vom 30. August 2023 , Licenza edilizia per il riattamento e il cambiamento di destinazione di una cantina - TI Tribunale d'appello (2023)
Licenza edilizia per il riattamento e il cambiamento di destinazione di una cantina